2009
DOI: 10.1016/j.jcmg.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Torsion

Abstract: During left ventricular (LV) torsion, the base rotates in an overall clockwise direction and the apex rotates in a counterclockwise direction when viewed from apex to base. LV torsion is followed by rapid untwisting, which contributes to ventricular filling. Because LV torsion is directly related to fiber orientation, it might depict subclinical abnormalities in heart function. Recently, ultrasound speckle tracking was introduced for quantification of LV torsion. This fast, widely available technique may contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(61 citation statements)
references
References 48 publications
0
60
0
1
Order By: Relevance
“…A reduced global longitudinal strain demonstrated a negative prognostic value in different diseases [18,19,20,21,22,23,24,25,26,27,28]; thus, the reduced value of longitudinal deformation in ALCAPA patients could be used to identify the subgroup of patients at higher risk. In agreement with previous studies [12], circumferential deformation was normal in our selected sample of ALCAPA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced global longitudinal strain demonstrated a negative prognostic value in different diseases [18,19,20,21,22,23,24,25,26,27,28]; thus, the reduced value of longitudinal deformation in ALCAPA patients could be used to identify the subgroup of patients at higher risk. In agreement with previous studies [12], circumferential deformation was normal in our selected sample of ALCAPA patients.…”
Section: Discussionmentioning
confidence: 99%
“…LV torsion is the result of the contraction of the left-handed subepicardial fibers while the right-handed subendocardial myocardial fibers counteract this torsion [28,29]. In ALCAPA patients, LV torsion was significantly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Six segments of the LV and septum were generated from apical 4‐chamber and short‐axis 2‐dimensional views (acquired at the mitral‐valve and apex levels) and averaged to determine global strain, strain rate, and displacement in the longitudinal, radial, and circumferential directions over 3 cardiac cycles using 2‐dimensional speckle tracking 17, 18, 21. Torsion was calculated as the difference between mitral and apical end‐systolic rotation (degrees) and normalized to both LV hypertrophy (wall thickness) and end‐diastolic chamber length as previously described 17, 22…”
Section: Methodsmentioning
confidence: 99%
“…Torsion has proven to be very useful for assessing the global function of the heart [82,83]. Several studies have shown its usefulness to display changes with age [84][85][86][87], hypertension [88], cardiomyopathy [89], obesity [90], and coronary heart disease [91][92][93].…”
Section: Figure 9 Dense Images With Radial Strain (Top Left) Circummentioning
confidence: 99%